Recent Approaches for the Topical Treatment of Psoriasis Using Nanoparticles - Krisztina Bodnár; Pálma Fehér; Zoltán Ujhelyi; Ildikó Bácskay; Liza Józsa (MDPI AG, 2024)
Psoriasis (PSO) is a chronic autoimmune skin condition characterized by the rapid and excessive growth of skin cells, which leads to the formation of thick, red, and scaly patches on the surface of the skin. These patches can be itchy and painful, and they may cause discomfort for patients affected by this condition. Therapies for psoriasis aim to alleviate symptoms, reduce inflammation, and slow down the excessive skin cell growth. Conventional topical treatment options are non-specific, have low efficacy and are associated with adverse effects, which is why researchers are investigating different delivery mechanisms. A novel approach to drug delivery using nanoparticles (NPs) shows promise in reducing toxicity and improving therapeutic efficacy. The unique properties of NPs, such as their small size and large surface area, make them attractive for targeted drug delivery, enhanced drug stability, and controlled release. In the context of PSO, NPs can be designed to deliver active ingredients with anti-inflammatory effect, immunosuppressants, or other therapeutic compounds directly to affected skin areas. These novel formulations offer improved access to the epidermis and facilitate better absorption, thus enhancing the therapeutic efficacy of conventional anti-psoriatic drugs. NPs increase the surface-to-volume ratio, resulting in enhanced penetration through the skin, including intracellular, intercellular, and trans-appendage routes. The present review aims to discuss the latest approaches for the topical therapy of PSO using NPs. It is intended to summarize the results of the in vitro and in vivo examinations carried out in the last few years regarding the effectiveness and safety of nanoparticles.